Estudios sistemático-hermenéuticos sobre el Vaticano II: Tres aportes relevantes en el período posconciliar - Schickendantz, Carlos Federico (Veritas, 2014)
The studies on the Vatican II focus in three areas that are closely linked: historical research, systematic studies in which particular emphasis is placed on the hermeneutic perspective, and research that lays emphasis on the multiple processes of reception in the regional contexts. This article deals only with the systematic aspect, taking into account three relevant contributions that marked the debate particularly around the eighties of the last century. These studies favored a qualitative leap in the hermeneutic understanding of the Council Firstly, the interpretation of Karl Rahner on a worldwide church. Secondly, the formulation of general principles of interpretation by the 1985 Synod. And finally, the specific hermeneutical criteria elaborated by Giuseppe Alberigo after the idea of Vatican II as an event that inspired the most relevant and detailed historical research of the nineties. The hermeneutical work produced during the beginning of our century has built on the foundations laid down by the three contributions discussed in this article.